2016
DOI: 10.1128/cvi.00613-15
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Hemagglutination Inhibition Assay for Influenza Serology Allows for High Reproducibility between Laboratories

Abstract: Standardization of the hemagglutination inhibition (HAI) assay for influenza serology is challenging. Poor reproducibility of HAI results from one laboratory to another is widely cited, limiting comparisons between candidate vaccines in different clinical trials and posing challenges for licensing authorities. In this study, we standardized HAI assay materials, methods, and interpretive criteria across five geographically dispersed laboratories of a multidisciplinary influenza research network and then evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 19 publications
2
55
0
Order By: Relevance
“…Reproducibility of HI is very low and sometimes cross reaction with other viruses also occurs. Standardization of HI assay can increase reproducibility of this test [58]. In a study, 120 people were tested for current strain of influenza using HI and CF and concluded that HI is more sensitive but less specific than CF [59].…”
Section: Hemagglutination Inhibitionmentioning
confidence: 99%
“…Reproducibility of HI is very low and sometimes cross reaction with other viruses also occurs. Standardization of HI assay can increase reproducibility of this test [58]. In a study, 120 people were tested for current strain of influenza using HI and CF and concluded that HI is more sensitive but less specific than CF [59].…”
Section: Hemagglutination Inhibitionmentioning
confidence: 99%
“…The role of other classes of antibodies, for example anti-neuraminidase (NA) antibodies, should not be ignored. Major global efforts in standardizing serologic assessment have contributed to a high reproducibility of HAI assays results [42, 43]. However, these results need to be carefully interpreted in seasons when antigenic drift is substantial.…”
Section: Discussionmentioning
confidence: 99%
“…The geometric mean increase was calculated as the rate between post- and pre-vaccination GMTs. The negative results obtained in HAI were assumed as half of the detection value (1/10) for the calculation of the GMTs [ 37 ]. Although there is a lack of consensus assuming a specific protective titer for AIV, a titer ≄1/40 was considered as protective in this work [ 38 ].…”
Section: Methodsmentioning
confidence: 99%